A Three‐Dimensional Origami Paper‐Based Device for Potentiometric Biosensing. Issue 42 (6th October 2016) - Ding, Jiawang; Li, Bowei; Chen, Lingxin; Qin, Wei
Abstract: Current paper‐based potentiometric ion‐sensing platforms are planar devices used for clinically relevant ions. These devices, however, have not been designed for the potentiometric biosensing of proteins or small molecule analytes. A three‐dimensional origami paper‐based device, in which a solid‐contact ion‐selective electrode is integrated with an all‐solid‐state reference electrode, is described for the first time. The device is made by impregnation of paper with appropriate bioreceptors and reporting reagents on different zones. By folding and unfolding the paper structures, versatile potentiometric bioassays can be performed. A USB‐controlled miniaturized electrochemical detector can be used for simple and in situ measurements. Using butyrylcholinesterase as a model enzyme, the device has been successfully applied to the detection of enzyme activities and organophosphate pesticides involved in the enzymatic system as inhibitors. The proposed 3D origami paper device allows the potentiometric biosensing of proteins and small molecules in a simple, portable, and cost‐effective way. Abstract : Assays on folding paper have potential : A three‐dimensional origami paper‐based device, in which a solid‐contact ion‐selective electrode is integrated with an all‐solid‐state reference electrode, has been developed for potentiometric biosensing.